A articulação entre ethos e efeitos de sentido: uma visão enunciativa sobre articuladores textuais, pronomes e verbos em textos do vestibular da UFSM - Silveira, Luciane Carlan da (2017)
This research aims to identify the categories of discursive-argumentative articulators, pronouns and verbs in texts of the opinion article genre, from the selective process (PS) of the Universidade Federal de Santa Maria (UFSM) of 2014, and to analyze the possible effects of sense arising from the use of these categories, collaborating to trace the discursive image of the speaker of the text. For this, the theoretical and methodological perspective that bases this study is the Linguistics of the Enunciation, because we understand that this perspective allows a better understanding about the image of a subject, the discursive ethos, through linguistic mechanisms used in the enunciation and recoverable from the Analysis of the marks left in the statement, its product. As theoretical basis, we take as guidelines the studies of Amossy (2014), Bagno (2013), Benveniste (1989; 1991), Cunha and Cintra (2008), Fiorin (2016), Flores et al. (2008; 2009; 2013), Moura Neves (2011), Koch and Elias (2016), among other authors. Methodologically, we have analyzed 23 copies of the opinion article genre. Quantitatively, the analysis of these texts consisted in the identification, description and categorization of textual articulators, pronouns and verbs. Qualitatively, according to the methods of enunciative transversality (FLORES, 2010) and the indicial paradigm (GINZBURG, 1989), reflected on the effects of meaning arising from the use of these categories that emerge from the textual materiality, contributing to the ethos of the speaker of the text. The results obtained in the quantitative-qualitative analysis explain explicitly that the relations of conjunction/addition, counterjunction/opposition and specification/exemplification of discursive-argumentative articulators are the most representative and present varying meanings for each enunciation. However, its use marks relations of meaning and makes the speaker's subjectivity emerge from some choices for the defense of his thesis. In terms of pronouns, whose predominance is the first person plural, and verbs, which has greater representation of the first and third persons of the plural, we note that, both categories, reveal degrees of subjectivity and objectivity of the speaker throughout the text. These degrees are related to the process of appropriation of language by the subject. Thus, by positioning itself in the third person plural, the speaker distances himself from the group of young people, if not belonging to him; which gives an effect of greater objectivity and authority to the text. However, by positioning itself in the first person plural, as in the case of pronouns, he places himself as belonging to the group of young people, approaching the interlocutor, as a "spokesman" of this group. Faced with this, in relation to the ethos, we find the tendency of four voices that compose it, which we name as: one dogmatic, one engaged, one experienced and one didatic. Finally, with this enunciative study, which considers the language in operation, with marks that emerge from the subject and contribute to tracing its discursive ethos, we aim, in a first moment, to make a linguistic reflection in a discursive materiality for, in a later study, to focus on a didactic vision, in the teaching of the mother language, above all, in the basic school, considering a articulation and/or an interdisciplinarity between Textual Linguistics and Linguistics of Enunciation.